Investigating the use of cuprizone and lysolecithin to model demyelination ex vivo in sagittal rat brain organotypic slice cultures - Hawker, Brooke; Connor, Bronwen; McCaughey-Chapman, Amy (Frontiers in Cellular Neuroscience, 2025)
IntroductionThe development of organotypic slice cultures of central nervous system (CNS) tissues has bridged the gap between simple in vitro cell cultures and complex in vivo whole animal studies. Organotypic brain slice cultures are a useful tool to study neurological disease, providing a more complex 3-dimensional system than standard 2-dimensional in vitro cell culture. In particular, organotypic brain slice cultures provide an excellent model to study the processes of demyelination and remyelination associated with neurological disease and injury. However, organotypic brain slice cultures are typically generated using coronal sectioning or regionspecific hippocampal or cerebellar tissue. We have previously reported the ability to generate sagittal organotypic brain slice cultures, allowing us to investigate the anterior-to-posterior integrity of the corpus callosum during demyelination and remyelination processes. To extend our sagittal organotypic brain slice culture model, this study compares the ability for two common demyelinating agents, cuprizone (CPZ) or lysolecithin (LPC), to induce demyelination of the corpus callosum.MethodsRat brain sagittal organotypic slice cultures were generated with clear visualization of the corpus callosum and treated either with CPZ (1 mM) or LPC (0.5 mg/mL).ResultsWe demonstrate that CPZ treatment induces acute demyelination followed by endogenous remyelination 1-week post-treatment. Conversely, we show that LPC treatment results in prolonged demyelination of the corpus callosum that is maintained 5 weeks post-treatment and is associated with an acute astroglia response.DiscussionOverall, this study demonstrates the use of CPZ and LPC to model either acute or prolonged demyelination in a sagittal organotypic brain slice culture system. These models provide a platform for studying acute and chronic demyelination and for testing new therapeutic approaches aimed at enhancing remyelination prior to conducting in vivo experiments.